2008
DOI: 10.1016/j.bbadis.2008.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Age-related reductions in expression of serum response factor and myocardin-related transcription factor A in mouse skeletal muscles

Abstract: The molecular signaling pathways linking the atrophy of skeletal muscle during aging have not been identified. Using reverse transcription (RT)-PCR, Western blotting, and immunofluorescence microscopy, we investigated whether the amounts of RhoA, RhoGDI, SRF, MRTF-A, and MyoD in the triceps brachii and quadriceps muscles change with aging in mice. Young adult (3 mo) and aged (24 mo) C57BL/6J mice were used. Senescent mice possessed many fibers with central nuclei in the quadriceps muscle. Western blotting usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
58
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 40 publications
(50 reference statements)
9
58
1
Order By: Relevance
“…Since SRF activities are known to deteriorate in some aging cells (53), it will be of great interest to explore potential contributions of age-dependent SRF activity changes in the aging retinal endothelium of human AMD patients. Furthermore, our work might suggest modulation of EC SRF activity, as well as elevation of thrombospondin activity, as therapeutic options for the treatment of some NV AMD pathologies, such as RAP and MacTel.…”
Section: Discussionmentioning
confidence: 99%
“…Since SRF activities are known to deteriorate in some aging cells (53), it will be of great interest to explore potential contributions of age-dependent SRF activity changes in the aging retinal endothelium of human AMD patients. Furthermore, our work might suggest modulation of EC SRF activity, as well as elevation of thrombospondin activity, as therapeutic options for the treatment of some NV AMD pathologies, such as RAP and MacTel.…”
Section: Discussionmentioning
confidence: 99%
“…64 Mice also show decreasing levels of SRF with advancing age. 65 One of the cofactors for SRF activity, MRTF-A, was also reduced in aged skeletal muscle. 65 Interestingly, transgenic mice overexpressing a dominant-negative form of MRTF-A show skeletal muscle atrophy.…”
Section: Blood Vesselsmentioning
confidence: 99%
“…65 One of the cofactors for SRF activity, MRTF-A, was also reduced in aged skeletal muscle. 65 Interestingly, transgenic mice overexpressing a dominant-negative form of MRTF-A show skeletal muscle atrophy. 61 Finally, skeletal muscle from a spontaneous mouse mutant (merosin, dy mice), which is a model for muscular dystrophy, showed attenuated SRF expression.…”
Section: Blood Vesselsmentioning
confidence: 99%
“…A key marker for SkM is MyoD, and SRF, which belongs to the MCM1-agamous-ARG80-deficiens-SRF (MADS)-box family of transcription factors, is known to directly regulate MyoD expression [48,49]. Very recent studies have suggested that the expression of this important SkM transcription factor is decreased in aged SkM [50,51]. We therefore assessed the role of SRF in the discrepant SkM differentiation capacity of hDE-MSCs versus adult BMMSCs.…”
Section: Expression Levels Of Srf Affect the Ability Of Differentiatimentioning
confidence: 99%